Optimasi Produksi Produk Sacha Inchi Oil dalam Pencapaian Keuntungan Maksimum di IKM Quilla Herbal Indonesia Sejahtera - Wahono, Syiffa Safiera; Andayani, Sri Ayu; Umyati, Sri; Purwanto, Muhamad Dendi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Sacha Inchi (Plukenetia volubilis L.) is a plant rich in omega-3, omega-6, and omega-9 fatty acids. Sacha Inchi Oil has many health benefits, such as lowering cholesterol, improving heart health, and improving brain function. IKM Quilla Herbal Indonesia Sejahtera is one of the agro-industries processing Sacha Inchi into Sacha Inchi Oil. However, IKM Quilla Herbal Indonesia Sejahtera has difficulty in optimizing and combining limited production factors. This study aims to identify the optimal production combination to get maximum profit. The data is processed using linear programming with simplex method. This research was conducted in Buahbatu District, Bandung City at IKM Quilla Herbal Indonesia Sejahtera. The selection of this research location was determined purposively. With the consideration that Quilla Herbal Indonesia Sejahtera is a company engaged in the cultivation, processing, and marketing of Sacha Inchi in Indonesia. From this study, the results show that the results of the linear programming simplex method with the help of the POM-QM application are to produce Sacha Inchi Oil 30 ml packaging as many as 415 bottles, 100 ml packaging as many as 159 (rounding) bottles, 250 ml packaging as many as 370 (rounding) bottles, 500 ml packaging as many as 166 bottles, and 1 liter packaging as many as 40 (rounding) bottles with the profit obtained as much as Rp155,776,022, so the increase in profit obtained is Rp130,734 per one production. Although it has not reached the optimal point, the number of products and profits obtained by Quilla under factual conditions is close to the optimal point.